Karshya -A Critical Review on Nutritional Deficiency as per Ayurveda (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda emphasize prevention over cure. A balanced diet with proper dietetic rule can help avoid a lot of common health concerns. The source of life for all living beings is food, growth, strength, intelligence, satisfaction, all are established in food. Food is significant as a nutritional source, as well as having therapeutic value, and it plays an important part in regaining strength lost due to the disease's detrimental effects throughout the post-treatment phase and also excess exercise, or addiction too. Ayurveda classic haphazardly explain nutritional issues. Each and every disease is due to faulty Ahara and Vihara. Ahara vidhi is equally important to get optimum benefits from consumed food. Childhood malnutrition is thought to be the cause of 35% of all fatalities in children under the age of five, as well as 21% of total worldwide disability-adjusted life years lost in children. Karshya not only concerns with weight loss, but also compares with malnutrition-like disorders. In Ayurveda, Karshya is a disease as well as cause, prodromal symptoms, feature of different diseases and bad prognostic sign. Karsha is also a physiological in Vataja prakriti individual. This illness is linked to growth and development issues in children and adolescence group. In adults, malnutrition results in weakness, fatigue, low immune response, protein, vitamin, minerals, fats deficiencies, and more prone to degenerative diseases. The aim of this review article is highlighted the Ayurvedic perspective on Karsha in term of malnutrition. All material for this article is collected from classical Ayurvedic texts. Understanding the cause and pathophysiology and accurate treatment as per Ayurved classics all are discussed here elaborately